Management of patients undergoing CAR-T cell therapy in Germany - Penack, Olaf; Dreger, Peter; Ajib, Salem; Ayuk, Francis; Baermann, Ben-Niklas; Bug, Gesine; Kriege, Oliver; Jentzsch, Madlen; Kobbe, Guido; Koenecke, Christian; Lutz, Mathias; Martin, Sonja; et al. (Oncology research and treatment, 2024)
Introduction: Chimeric antigen receptor positive T cell (CAR-T cell) treatment became standard therapy for relapsed or refractory hematologic malignancies, such as non-Hodgkin’s lymphoma and multiple myeloma. Owing to the rapidly progressing field of CAR-T cell therapy and the lack of generally accepted treatment guidelines, we hypothesized significant differences between centers in the prevention, diagnosis, and management of short- and long-term complications. Methods: To capture the current CAR-T cell management among German centers to determine the medical need and specific areas for future clinical research, the DAG-HSZT (Deutsche Arbeitsgemeinschaft für Hämatopoetische Stammzelltransplantation und Zelluläre Therapie; German Working Group for Hematopoietic Stem Cell Transplantation and Cellular Therapy) performed a survey among 26 German CAR-T cell centers. Results: We received answers from 17 centers (65%). The survey documents the relevance of evidence in the CAR-T cell field with a homogeneity of practice in areas with existing clinical evidence. In contrast, in areas with no - or low quality - clinical evidence, we identified significant variety in management in between the centers: management of cytokine release syndrome, immune effector cell-related neurotoxicity syndrome, IgG substitution, autologous stem cell backups, anti-infective prophylaxis, and vaccinations. Conclusion: The results indicate the urgent need for better harmonization of supportive care in CAR-T cell therapies including clinical research to improve clinical outcome.